The Big old bear who swallowed a fly - Phillips, Trish (London : Little Tiger Press, 2006)
There was an old bear with a big rumbly tummy. He stoped a fly and cried. " Fly dinner -YUMMY".
A Pop-up story.
Keywords: Pop-up books, English; Toy and movable books, English; 3D books, English; Bears -- Fiction; Fly -- Fiction; Jungle -- Fiction